The Role of Scientific Literacy Instruments For Measuring Science Problem Solving Ability - Rizqi Afnan; Munasir Munasir; Mohammad Budiyanto; Mochammad Izzur Rizky Aulia (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
A critical aspect of measuring judgment in the 21st century is scientific literacy. In addition to the scientific literacy aspect as part of the grade 21 skills assessment, there are other essential aspects, namely student problem-solving skills. Based on the articles collected, it can be concluded that to meet the necessities of life in various situations in the global era, Literacy ability is a fundamental thing that all students must own. The role of scientific literacy instruments is needed to measure students' science problem-solving abilities. Because scientific literacy is an individual's ability to identify, explain and conclude scientific evidence by using the ability to solve problems based on how to understand, plan, solve, and reassess. This can be seen from the many theories and teaching methods that support the results obtained from the forty-four journals reviewed. The criteria for the articles used are those published in 2017-2022. The purpose of this article review is to determine the role of scientific literacy instruments in measuring students' problem-solving abilities by using a literature review that gathers sources from several previous articles.